Micropore clogging by leachable pyrogenic organic carbon: A new perspective on sorption irreversibility and kinetics of hydrophobic organic contaminants to black carbon. (January 2017) - Wang, Bingyu; Zhang, Wei; Li, Hui; Fu, Heyun; Qu, Xiaolei; Zhu, Dongqiang
Abstract: Black carbon (BC) plays a crucial role in sequestering hydrophobic organic contaminants in the environment. This study investigated key factors and mechanisms controlling nonideal sorption (e.g., sorption irreversibility and slow kinetics) of model hydrophobic organic contaminants (nitrobenzene, naphthalene, and atrazine) by rice-straw-derived BC. After removing the fraction of leachable pyrogenic organic carbon (LPyOC) (referring to composites of dissoluble non-condensed organic carbon and associated mineral components) with deionized water or 0.5 M NaOH, sorption of these sorbates to BC was enhanced. The sorption enhancement was positively correlated with sorbate molecular size in the order of atrazine > naphthalene > nitrobenzene. The removal of LPyOC also accelerated sorption kinetics and reduced sorption irreversibility. These observations were attributed to increased accessibility of BC micropores initially clogged by the LPyOC. Comparison of BC pore size distributions before and after atrazine sorption further suggested that the sorbate molecules preferred to access the micropores that were more open, and the micropore accessibility was enhanced by the removal of LPyOC. Consistently, the sorption of nitrobenzene and atrazine to template-synthesized mesoporous carbon (CMK3), a model sorbent with homogeneous pore structures, showed decreased kinetics, but increased irreversibility by impregnating sorbent pores with surface-grafted alkylamino groups and by subsequent loading of humic acid. These findings indicated an important and previously unrecognized role of LPyOC (i.e., micropore clogging) in the nonideal sorption of organic contaminants to BC. Graphical abstract: Highlights: LPyOC clogged BC micropores and hindered the accessibility to organic contaminants. LPyOC removal accelerated sorption kinetic and reduced sorption irreversibility to BC. The pore-clogging mechanism could be well described by model CMK3 sorbents. LPyOC plays an unrecognized important role in the sorption-desorption process to BC. Abstract : Removal of leachable pyrogenic organic carbon accelerated sorption kinetics and reduced sorption irreversibility of organic contaminants to bulk rice residue-derived black carbon.